“文章四友”新论：以李峤、崔融之应用文书写为探讨中心 = New perspectives on “Wenzhang siyou” : focus on Li Qiao and Cui Rong’s practical prose - 曲景毅 Qu, Jingyi (2016)
文學史上向以李嶠、崔融、蘇味道、杜審言并稱「文章四友」，卻甚少關注其文章成就。本文以崔融、李嶠應用文書寫為探討中心，指出高宗、武后時期以崔融、李嶠為代表的「大手筆」作家因襲六朝綺靡華贍的風氣，風雅之道掃地，廟堂文風一度頗為不振。就文章的內容而言，徇功稱美、頌德稱獎的華而不實之辭大行其道，較為缺乏政教意義與真情實感的流露。李嶠、崔融的頌體文盡顯詞臣面貌，因時代風會祥瑞觀念大量體現。當然，他們又是頌體與諫議之複合體，二人的奏議文為其文章增添了一種實在與亮色。總體來說，李嶠是撰寫謙詞雅語的行家裏手，頌揚主上極盡鋪張華麗之能事；與其相類，崔融亦立辭比事，潤色太平之業，但崔融的文章引經據典，博聞廣記，擅長使用「連珠體」式的排比句，尤喜愛三字句間插句中，句式富於變化。以文學成就而言，崔融較李嶠略勝一籌。本文由此申發認為「文章四友」中的「文章」兼指詩賦與文章，且偏重于指文，「崔、李、蘇、杜」的排序與其文章成就及在當時被認可的程度基本吻合。LI Qiao李嶠, CUI Rong崔融, SU Weidao蘇味道and DU Shenyan杜審言are called “Wenzhang siyou”文章四友 (Four Literary Friends) in the history of Chinese literature. However, there is very little research on their achievements of prose writing. The paper focuses on LI Qiao and CUI Rong’s practical prose since SU and Du’s prose was not reserved. In LI and CUI’s prose, excessively beautiful and parallel style goes from bad to worse in general. Their ode declarations, merit epitaphs and mourning appointments express their appearance of palace writers totally and become continuation of the Six Dynasties. There are no political educated meanings and true feelings but lots of auspicious ideas which be used to praise Emperor Wu武后in their prose writings. However, their memorial discussions with somewhat implications could be the “bright color” for them. Comparatively speaking, CUI’s literary achievement is better than LI’s for some reasons. Firstly, Cui’s prose richly embellishes with allusions and quotations. Secondly, CUI is very good at parallelism just like Lianzhu 連珠style. Thirdly, especially tending three-word sentence makes his syntax more changeable. The paper further talks about “wenzhang”文章in “Wenzhang siyou” that includes poetry and prose, mainly indicates the latter. And the ranking of “Wenzhang siyou” is consistent with the achievements of the four writers.